Isolation of subgenus B adenovirus during a fatal outbreak of enterovirus 71-associated hand, foot, and mouth disease in Sibu, Sarawak. - Cardosa, Mary Jane; Krishnan, Shekhar; Tio, Phaik Hooi; Perera, David; Wong, See Chang (Science Direct, 1999)
BACKGROUND: In mid-1997, several children died in Sarawak, Malaysia, during an epidemic of enterovirus-71 (EV71) hand, foot, and mouth disease. The children who died had a febrile illness that rapidly progressed to cardiopulmonary failure and the cause was not satisfactorily resolved. We describe the isolation and identification of a subgenus B adenovirus from the children who died. METHODS: We studied two groups of children presenting to Sibu Hospital from April 14 to Sept 30, 1997. For children who died, the inclusion criterion was death after febrile illness, and for those who did not die it was acute flaccid paralysis (AFP). Serum and cerebrospinal fluid samples were tested for IgM antibodies to Japanese encephalitis and dengue viruses. Viruses isolated were identified by immunofluorescence, reverse-transcriptase PCR, or PCR and DNA sequencing. FINDINGS: Enterovirus was isolated in three (19%) of 16 children who died and in none of the eight surviving children with AFP. However, an agent that was initially difficult to identify was found in ten (63%) children who died and five (63%) surviving children who had AFP. The agents isolated from ten (66.7%) of these 15 children were eventually identified as adenoviruses and were isolated mainly from clinically important sterile sites or tissues. All the enterovirus-positive children who died had this second agent. INTERPRETATION: Our data raises doubts that EV71 was the only aetiological agent in these deaths.